The origins of Judaism an archaeological-historical reappraisal - Adler, Yonatan 1976- (Yale University Press, 2022)
"Throughout much of history, the Jewish way of life has been characterized by strict adherence to the practices and prohibitions legislated by the Torah: dietary laws, ritual purity, circumcision, Sabbath regulations, holidays, and more. But precisely when did this unique way of life first emerge, and why specifically at that time? In this revolutionary new study, Yonatan Adler methodically engages ancient texts and archaeological discoveries to reveal the earliest evidence of Torah observance among ordinary Judeans. He examines the species of animal bones in ancient rubbish heaps, the prevalence of purification pools and chalk vessels in Judean settlements, the dating of figural representations in decorative and functional arts, evidence of such practices as tefillin and mezuzot, and much more to reconstruct when ancient Judean society first adopted the Torah as authoritative law. Focusing on the lived experience of the earliest Torah observers, this investigative study transforms much of what we thought we knew about the genesis and early development of Judaism."--Dust jacket
Keywords: Geschichte; Entstehung; Judentum; Thora; Archäologie; Judaism / History / Post-exilic period, 586 B.C.-210 A.D.; Judaism / History / To 70 A.D.; Jews / History / 586 B.C.-70 A.D.; Jews / History / To 70 A.D.